2007
DOI: 10.1080/17483100701714733
|View full text |Cite
|
Sign up to set email alerts
|

Consumer design priorities for upper limb prosthetics

Abstract: Design priorities reflect consumer goals for prosthesis use and vary depending on the type of prosthesis used and age. Future design efforts should focus on the development of more light-weight, comfortable prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
405
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(420 citation statements)
references
References 45 publications
11
405
3
1
Order By: Relevance
“…In the past two decades, many new materials have become available that can be used for mechanism, bearings, gloves, etc. Meanwhile, various user studies clearly mapped the needs of the prosthesis user [4,17]. However, comparisons between our results and Corin et al's results showed no significant difference for the required work or pinch forces for the hooks or for the hands (Figure 8(a) and 8(b)).…”
Section: Past Present Futurecontrasting
confidence: 55%
“…In the past two decades, many new materials have become available that can be used for mechanism, bearings, gloves, etc. Meanwhile, various user studies clearly mapped the needs of the prosthesis user [4,17]. However, comparisons between our results and Corin et al's results showed no significant difference for the required work or pinch forces for the hooks or for the hands (Figure 8(a) and 8(b)).…”
Section: Past Present Futurecontrasting
confidence: 55%
“…A BP prosthetic hand requires up to 2,292 Nmm of energy to pinch 15 N, a user effort that is uncomfortably high [8]. User needs of people with hand amputation include a higher pinch force [9], a lower activation effort [8], and a lower hand mass [10]. To achieve these goals, an efficient energy transmission is required.…”
Section: Problemmentioning
confidence: 99%
“…However, obtaining full representation of shapes compatible with anthropometric data of a patient requires using additional technologies. In case of the cosmetic prostheses not only the comfortable fitting, but also the visual aspect is important for the patient [1]. In case of patients having one of the limbs, a mirror image of this limb can be used for making the prosthesis.…”
Section: Theoretical Informationmentioning
confidence: 99%